Sex-related differences in body compostion, power, sprint ability, and agility among NCAA Division I basketball players - Johnson, Q.; Trevino, M.; Dawes, J.; Boolani, A. (The Journal of Strength and Conditioning Research, 2021)
Basketball is a very dynamic sport. Often times, success is determined not only by the level of aerobic conditioning, but also by the degree to which an athlete can express their potential anaerobically via explosive strength, power, speed, and agility. Although the demands of the sport are similar, anaerobic capacities may differ between sexes. Purpose: To investigate sex-related differences in measures of body composition, power, sprint, and agility in elite level male and female basketball players. Methods: Ten healthy men (X¯ ± SD; age = 21.1 ± 1.1 years, body mass = 95.3 ± 10.9 kg, height = 197.4 ± 9.6 cm) and 8 healthy women (age = 19.5 ± 0.8 years, body mass = 71.2 ± 10.1 kg, height = 175.2 ± 6.1 cm) NCAA Division I basketball players volunteered for this investigation. Subjects were tested to for the following: (a) height, (b) body mass (c) body fat percentage, (d) vertical jump, (e) standing broad jump, (f) one-repetition maximum (1RM) power clean, (g) full court sprint, and (h) a t-drill. After body composition measures were taken, subjects were taken through a dynamic warm-up protocol which included general and sport-specific upper and lower-extremity activation movements as well as core activation movements. After their warm-up, subjects' vertical and standing broad jump were assessed. For each assessment, subjects were given 3 attempts with the highest attempt being reported. Next, subjects were given attempts at 90% of their previously recorded 1RM power clean. After each successful attempt, subjects were given 5-minutes of rest and the weight was increased by 2.27 kg. To end, subjects were given 3 attempts on the full-court sprint and t-drill assessments. The fastest attempt was reported. Mann-Whitney U were conducted to analyze data. In addition, Pearson product-moment correlations were used to determine the relationships among all performance variables and body fat percentage. An alpha level of 0.05 was used to determine statistical significance. Results: For all measures except for t-drill performance (p > 0.05), there were sex-related differences. Men were significantly taller (p < 0.001), had more body mass (p < 0.001), less body fat percentage (p < 0.05), higher 1RM power clean values (p < 0.001), jumped higher (p < 0.001) and further (p < 0.001), and completed their full court sprint (p < 0.05) faster than women. Additionally, there were significant correlations between body fat percentage, power clean, vertical jump, and standing broad jump (p < 0.001-0.021, r = -0.655-0.855); however; there were no relationships between body fat percentage, full court sprint or the t-drill (p = 0.089-0.989, r = -0.391-0.438). Conclusions: Men performed significantly better than women in linear movements however, there was no difference in agility. Men were significantly taller with more lean muscle mass, which may influence their performance in linear movements as they may have significantly better leverage with higher muscle mass in their lower extremities. Practical Application: While the female basketball athlete generally performs the same movements as their male counterparts, it appears that they are less efficient in executing these movements. However, with a designated approach by the certified strength and conditioning specialist which focuses on developing lower-body power in each plane of motion and sprinting ability this can be modified.